Bioconversion and performance of Black Soldier Fly (Hermetia illucens) in the recovery of nutrients from expired fish feeds. (15th March 2022) - Rodrigues, Daniela P.; Calado, Ricardo; Pinho, Marisa; Rosário Domingues, M.; Antonio Vázquez, José; Ameixa, Olga M.C.C.
Highlights: Expired marine aquafeeds can be recycled by Black Soldier Fly (BSF) n -3 fatty acids bioaccumulation is modulated by replacement level and time. BSF is a promising alternative ingredient for marine aquafeeds. Abstract: In modern aquaculture systems, feed is the main source of the waste being produced, including expired aquafeeds. There is a link between the expiration date of aquafeeds enriched with fish oil for marine fish and the observation of several physical and microbiological changes. Among these, lipid oxidation is worth highlighting, as this process is responsible for the loss of palatability of aquafeeds, which can lead to feeding rejection by the species being farmed. In this study, we used an expired fish aquafeed, which otherwise would be discarded as waste, as a substrate to feed Black Soldier Fly (BSF) larvae. Different replacement levels of expired aquafeed were used which unravelled the amount of n -3 fatty acids added to larval tissues of BSF larvae after 2, 7, and 10 days of feeding. Our results also showed that shorter trials and higher diet replacement levels induced a deleterious effect on final larval weight. Furthermore, amino acid and fatty acid larval contents were shaped by the supplied diet, with results supporting the inclusion of BSF meal in aquafeeds, due to the levels of lysine (5.6–8.9%), methionine (1.9–3.2%), and omega-3 fatty acids (14.5%) recorded. These results demonstrate that the re-introduction of an expired resource aiming to diversify the source of aquafeeds raw materials can be safely achieved through BSF biotransformation. Overall, BSF larvae can successfully recover important nutrients for aquafeeds targeting marine species and foster the production of value-added insects under a circular bioeconomy framework.